Crime Scene in the Czech Republic: German in the Dead Corner - Čapek, Jan (Germanistinnen und Germanisten im Beruf – zwischen Ausbildung und Realität, 2020)
The article describes the level and the tendencies of German as a language of instruction in the Czech school system and compares them with the needs of business that are much higher than the school system provides. The current situation on the labour market in the Czech Republic, where not only skilled workers with the appropriate knowledge of German, but also other workers are missing, is evaluated. This obvious discrepancy between the number of pupils and students (primary schools, secondary schools, universities) who have an adequate command of German and the number of staff that is required by business and administration (industrial production, energy industry, banks, trade, state administration and archives) is proved and justified. The case example of call-centres explains how the current German speaking employees have to be trained, or some other ones have to be brought from abroad.